The hedgehog and the fox : an essay on Tolstoy's view of history - Berlin, Isaiah, 1909-1997 (Princeton University Press, 2013)
""The fox knows many things, but the hedgehog knows one big thing."" This ancient Greek aphorism, preserved in a fragment from the poet Archilochus, describes the central thesis of Isaiah Berlin's masterly essay on Leo Tolstoy and the philosophy of history, the subject of the epilogue to War and Peace. Although there have been many interpretations of the adage, Berlin uses it to mark a fundamental distinction between human beings who are fascinated by the infinite variety of things and those who relate everything to a central, all-embracing system. Applied to Tolstoy, the saying illu